2017
DOI: 10.5539/jas.v9n13p145
|View full text |Cite
|
Sign up to set email alerts
|

Current Knowledge on Honey and Its Derivatives with Genomic Stability: A Mini Review

Abstract: Genome health is an important factor that plays a role in various degenerative diseases. Instability of genome is the prevalence of mutation within the genome such as changed in nucleic acid and chromosomal arrangement and also the presence of abnormal number of chromosome in cell. Therefore, several method were used to overcome this problem and one of them is by using natural product such as honey, propolis, bee pollen and royal jelly that is high in antioxidant. Those are products that derive from honey bee … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…It has been known that oxidative stress is one of the major causes of mutation and is involved in all stages of carcinogenesis during neoplasm formation ( Kryston et al, 2011 ). Recent studies have shown that oxidative stress can cause genomic instability and gene silencing in cells, thus leading to the progression of degenerative diseases and speed up the aging process in the body ( Lombard et al, 2005 , Lu et al, 2004 , Yaacob et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been known that oxidative stress is one of the major causes of mutation and is involved in all stages of carcinogenesis during neoplasm formation ( Kryston et al, 2011 ). Recent studies have shown that oxidative stress can cause genomic instability and gene silencing in cells, thus leading to the progression of degenerative diseases and speed up the aging process in the body ( Lombard et al, 2005 , Lu et al, 2004 , Yaacob et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Not many studies have, up to now, investigated the influence of honey at the genome and cell level. In 2017, Yaacob et al [15] published an extensive review that provides good insight into the existing studies that investigated the association between honey and genomic stability. Evidently, there is no specific rationale for investigating and establishing the protective effects for well-known honey types that humankind has used since ancient times.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, numerous studies led to the differentiation of biological activity results related to propolis [8]. This natural product has been widely used for a variety of purposes in folk medicine as cardiovascular and gastrointestinal disease, respiratory tract infections, immune system support, antioxidant anti-inflammatory, antimicrobial, and antiviral agent [3,9,10,11]. Moreover, in recent years there are also several studies related to the antigenotoxic activity of propolis [12,13,14,15].…”
Section: Introductionmentioning
confidence: 99%